The sword in the stone : lithic raw material in the Middle Stone Age at Pinnacle Point Site 5-6, southern Cape, South Africa - Brown, Kyle S (Department of Archaeology, 2014)
This thesis presents a description and analysis of the lithic artefacts from the recently excavated site of Pinnacle Point 5-6, Mossel Bay, from a sequence dating between ~50-85ka. PP5-6 has been excavated to the highest contemporary standards, enabling a more detailed analysis of the lithics than is possible for Klasies. Although the PP5-6 lithic sequence conforms with the overall trends of MSA artifact manufacture, a number of differences from other sites are identified here for the first time - a significant step towards understanding behavioral variability and complexity among early modern humans.